Musculoskeletal ultrasound for pain - Uslu, Emine Yildirim; Yildirim, Mustafa (Nova Science Publishers Inc., 2025)
In this section, we examined the use of ultrasonography, which has increasing importance for the musculoskeletal system, in different tissues such as joints, enthesis, bones, tendons, ligaments, and peripheral nerves. We also evaluated the pathologies of the musculoskeletal system that can be diagnosed with ultrasonography and the place of ultrasonography in pain management. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Musculoskeletal system; Pain; Ultrasonography